Molecular simulations of nitrogen-doped hierarchical carbon adsorbents for post-combustion CO2 capture. Issue 41 (10th October 2016) - Psarras, Peter; He, Jiajun; Wilcox, Jennifer
Abstract : A present challenge in the mitigation of anthropogenic CO2 emissions involves the design of less energy- and water-intensive capture technologies. Abstract : A present challenge in the mitigation of anthropogenic CO2 emissions involves the design of less energy- and water-intensive capture technologies. Sorbent-based capture represents a promising solution, as these materials have negligible water requirements and do not incur the heavy energy penalties associated with solvent regeneration. However, to be considered competitive with traditional technologies ( i.e., MEA capture), these sorbents must exhibit a high CO2 loading capacity and high CO2 /N2 selectivity. It has been reported that ultramicroporous character and surface nitrogen functionality are of great importance to the enhancement of CO2 capacity and CO2 /N2 selectivity. However, the role of pore size in combination with surface functionality in the enhancement of these properties remains unclear. To investigate these effects, grand canonical Monte Carlo (GCMC) simulations were carried out on pure and N -functionalized 3-layer graphitic slit-pore models and compared to experimental results for two high performing materials reported elsewhere. We show that the quaternary, pyridinic, and especially the oxidized pyridinic group lend to enhanced performance, with the latter providing exceptional CO2 loading (4.31 mmol g −1 ) and CO2 /N2 selectivity (138.3 : 1). Increasing surface nitrogen content resulted in enhanced loading and excellent CO2 /N2 selectivity (45.8 : 1–55.9 : 1), provided that the sorbent has significant ultramicroporous character. Additionally, we elucidate a threshold pore width, under which N -functionalization becomes increasingly influential on performance parameters, and show how this threshold changes with application (PC vs. NGCC capture). Finally, we propose that an alternative functionality – the nitroso group – may be responsible for the enhanced performance of some recent materials reported in the literature.